2012
DOI: 10.1073/pnas.1108225109
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial hexokinase II (HKII) and phosphoprotein enriched in astrocytes (PEA15) form a molecular switch governing cellular fate depending on the metabolic state

Abstract: The metabolic state of a cell is a key determinant in the decision to live and proliferate or to die. Consequently, balanced energy metabolism and the regulation of apoptosis are critical for the development and maintenance of differentiated organisms. Hypoxia occurs physiologically during development or exercise and pathologically in vascular disease, tumorigenesis, and inflammation, interfering with homeostatic metabolism. Here, we show that the hypoxia-inducible factor (HIF)-1-regulated glycolytic enzyme he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 44 publications
(72 reference statements)
3
86
0
Order By: Relevance
“…2B). Interestingly, the glucose dependence of mitochondrial localization has also been reported for HK2, which is localized to the mitochondria in the presence of glucose but moves to the cytosol when glucose is removed (2,12). Consistently, we also found that the removal of glucose resulted in some dissociation of HK2 and a mitochondrial marker (mtHsp70), particularly in 0.1% O 2 , although even under these conditions, some HK2 remained at the mitochondria (Fig.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…2B). Interestingly, the glucose dependence of mitochondrial localization has also been reported for HK2, which is localized to the mitochondria in the presence of glucose but moves to the cytosol when glucose is removed (2,12). Consistently, we also found that the removal of glucose resulted in some dissociation of HK2 and a mitochondrial marker (mtHsp70), particularly in 0.1% O 2 , although even under these conditions, some HK2 remained at the mitochondria (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Although HK2 can protect cells from hypoxic cell death, this activity is lost in the absence of glucose (12), conditions under which HK2 becomes dissociated from the mitochondria (2). Consistently, we have also shown that the translocation of TIGAR to the mitochondria and the binding to HK2 depend on glucose availability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…New insight into the mechanisms of HK2-mediated protection has been provided by a recent study by Mergenthaler et al published in The Proceedings of the National Academy of Sciences [9]. Here, overexpression of HK2 was shown to protect cultured neurons against combined Oxygen-Glucose Deprivation (OGD) as well as just Oxygen Deprivation (OD) alone.…”
mentioning
confidence: 97%